An overview of sales and marketing strategies of "Value First Digital Media Bangladesh Ltd" during Covid'19 pandemic - Nidhi, Syeda Nusrat Taznin (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.